Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/jsfa.12778
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive components and nutritional properties of fiber‐rich cookies produced with different parts of oleaster (Elaeagnus angustifolia L.)

Abstract: BACKGROUNDOleaster (Elaeagnus angustifolia L.) possesses exocarp and endocarp layers enriched with abundant phytochemicals and fiber. Flours produced in different parts of oleaster were used in cookie formulation to improve the bioactive components and nutritional properties of cookies.RESULTSThe rheological properties of composite flours containing varying levels of oleaster exocarp flour (O'EX‐F) and endocarp flour (O'EN‐F), ranging from 0% to 30%, were assessed using Mixolab (Chopin Technologies, Villeneuve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It can be due to the interaction between whole wheat (starch) and increased phenolic compounds (nonstarch compounds) due to BG substitution, forming a gluten network that enhances dough strength by decreasing flexibility . The formation of composite flour cookies in other studies reported similar results . The increased crumbliness of cookies could be due to the disturbance in the gluten network by the incorporation of BG powder that lessened its strength …”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It can be due to the interaction between whole wheat (starch) and increased phenolic compounds (nonstarch compounds) due to BG substitution, forming a gluten network that enhances dough strength by decreasing flexibility . The formation of composite flour cookies in other studies reported similar results . The increased crumbliness of cookies could be due to the disturbance in the gluten network by the incorporation of BG powder that lessened its strength …”
Section: Resultsmentioning
confidence: 68%
“…7 The formation of composite flour cookies in other studies reported similar results. 27 The increased crumbliness of cookies could be due to the disturbance in the gluten network by the incorporation of BG powder that lessened its strength. 28 Color Analysis of Cookies.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%